ISOLATION AND CULTURE OF Celosia cristata L. CELL SUSPENSION PROTOPLASTS - Retno Mastuti; Hiroshi Miyake; Takeshi Taniguchi; Yoji Takeoka (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2003)
Developmental competence of Celosia cristata L. cell suspension-derived protoplasts was investigated. The protoplasts were isolated from 3- to 9-d old cultures in enzyme solution containing 2% (w/v) Cellulase YC and 0.5% (w/v) Macerozyme R-10 which was dissolved in washing solution (0.4 M mannitol and 10 mM CaCl2) at pH 5.6 for 3 hours. The highest number of viable protoplasts was released from 5-d old culture of a homogenous cell suspension. Subsequently, three kinds of protoplast culture media were simultaneously examined with four kinds of concentration of gelling agent. Culturing the protoplasts on KM8p medium solidified with 1.2% agarose significantly enhanced plating efficiency as well as microcolony formation. Afterwards, the microcalli actively proliferated into friable watery callus when they were subcultured on MS medium supplemented with 0.3 mg/l 2,4-D and 1.0 mg/l kinetin. Although the plant regeneration from the protoplasts-derived calli has not yet been obtained, the reproducible developmental step from protoplasts to callus in this study may facilitate the establishment of somatic hybridization using C. cristata as one parent.